Kelayakan Usaha Tani Bawang Merah Semi Organik Petani Milenial dan Non Milenial di Kalurahan Selopamioro Kapanewon Imogiri Kabupaten Bantul - Nita, Anna Tria; Kusumaningsih, Asih; Jamhari, Jamhari (Hasanuddin University, 2025)
Shallots are one of the horticultural commodities with significant market potential and high economic value. This study aims to: (1) identify differences in cost, revenue, income, and profit; and (2) analyze the differences in farming feasibility between millennial and non-millennial farmers in Selopamioro Village, Imogiri Sub-district, Bantul Regency. The research location was selected using a purposive sampling method, with a total of 24 millennial farmers and 30 non-millennial farmers as respondents. The first objective was analyzed using cost, revenue, income, and profit calculations, followed by an Independent Sample t-Test to statistically assess the differences. Meanwhile, farming feasibility was analyzed using the π/C Ratio. The results show that semi-organic shallot farming costs incurred by millennial farmers are higher than those of non-millennial farmers. However, there were no significant differences in revenue, income, profit, or π/C ratio between the two groups, indicating that semi-organic shallot farming is feasible for both millennial and non-millennial farmers.